Zinc-Based Semiconductors/Polymer Thin Films Junction for Photovoltaic Application - Souad Al-bat’hi; K. A. Buhari; M. I. Latiff (International Journal of Photoenergy)
Thin films of ZnO and ZnTe semiconductors were deposited on ITO conducting glass substrates by sputtering and electrodeposition techniques, respectively. On the other hand, thin films of ion conducting solid polymer electrolyte were prepared by solution cast technique. The polymer is a blend of 50 wt% polyethylene oxide and 50 wt% chitosan. To provide redox couple (I−/I3−), the polymer was complexed with ammonium iodide NH4I with addition of few crystals of iodine I2. Ammonium iodide NH4I was added to the solution in different amounts (wt%) weight ratios to supply the charge carriers for the polymer electrolytes. The highest ionic conductivity of the polymer electrolyte was 1.18×10−5 S cm−1 at room temperature. Structural and optical properties of the semiconductor thin films were characterized by X-ray diffractometer and UV-Vis spectrophotometer. The XRD shows crystalline structures for both ZnO and ZnTe thin films. The UV-Vis shows direct energy gaps EZnO of 3.1 eV and EZnTe of 2.2 eV. The polymer film was sandwiched between the ZnO and ZnTe semiconductors to form ITO/ZnO/polymer/ZnTe/ITO double-junction photovoltaic cell, and the photovoltaic properties were studied. The highest open-circuit voltage 𝑉oc, short-circuit current density 𝐽sc, and fill factor FF of the fabricated cells are 0.5 V, 55 μA cm−2, and 27%, respectively.